A study on the usage of check-out bags in stores: the law and policy in Malaysia and the United States / Nur Atiqah Mohd Marzlan, Nur Farhana Md Kher and Suzairin Othman - Mohd Marzlan, Nur Atiqah; Md Kher, Nur Farhana; Othman, Suzairin (Faculty of Law, 2010)
This paper studies the usage of check out bags in stores: the law and policy in Malaysia and the United States. To extract and gain relevant information regarding this issue, semi-structured interviews were conducted with two officers that are directly involve with the policy in Malaysia to supplement the library based information. Factors like economic issue, environment and the mind-set of Malaysian were seen as sufficient enough issues to slow down the process of making the policy and implementing it as law in Malaysia. Our study also signifies that although it is too soon for Malaysia to totally ban the usage of plastic bags, worldwide statistics have proven the fact that it can be done and there are big reductions on waste made from plastic bags. Finally, our findings indicate that even though there is a large reduction in number of waste after the implementation of this policy in Selangor and Penang, the end result on whether this policy will be made to all states in Malaysia or implementing it as law will rest on the government of Malaysia to decide.